2022
DOI: 10.1002/pts.2641
|View full text |Cite
|
Sign up to set email alerts
|

Field assessment of horizontal accelerations using air ride suspension trailers

Abstract: Current laboratory tests designed to evaluate package and unit load systems focus strictly on the intensity of vertical orientation. However, due to an increased demand for source reduction and the light-weighting of packaging components, unit loads are becoming more susceptible to the horizontal forces encountered during transport.Understanding the field measured acceleration levels is critical to developing accurate laboratory test simulations to examine unit load rigidity. This paper uses horizontal acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
5
3
3
Order By: Relevance
“…The statistical mean of the average values for the braking and acceleration manoeuvres were 0.25 and 0.28 g, respectively. These mean values again align with previous researches performed by Dunno and Ge,13,20 who reported an average acceleration of 0.29 g from the straight delivery box truck, and Nolot et al, 21 who reported average accelerations ranging from 0.27 to 0.33 g. This average is lower than the EUMOS or ISO test protocols, which use target thresholds of 0.8 and 1.0 g. However, if only the maximum average acceleration values from this study are considered, even then the data do not correlate with the recommended test conditions.…”
Section: Average Acceleration Of the Eventsupporting
confidence: 91%
“…The statistical mean of the average values for the braking and acceleration manoeuvres were 0.25 and 0.28 g, respectively. These mean values again align with previous researches performed by Dunno and Ge,13,20 who reported an average acceleration of 0.29 g from the straight delivery box truck, and Nolot et al, 21 who reported average accelerations ranging from 0.27 to 0.33 g. This average is lower than the EUMOS or ISO test protocols, which use target thresholds of 0.8 and 1.0 g. However, if only the maximum average acceleration values from this study are considered, even then the data do not correlate with the recommended test conditions.…”
Section: Average Acceleration Of the Eventsupporting
confidence: 91%
“…Overall, the intersection and roundabouts have larger lateral acceleration and duration than that of other two categories; 95% of the lateral acceleration during turnings ranged from 0.24 to 0.36 g for the truck and 0.21 to 0.35 g for the trailer (Figure 17). These values align closely with the range of 0.30 to 0.42 g reported in previous studies [9,10]. The mean lateral acceleration for the truck and trailer in this study ranged from 0.15 to 0.18 g and 0.13 to 0.18 g, respectively.…”
Section: Cumulative Percentage Of Long-duration Eventssupporting
confidence: 91%
“…It is worth noting that only three instances, representing 0.16% of all braking events, exceeded 0.40 g, which aligns with Klusmeyer et al's report indicating that only 0.11% of brake deceleration events surpassed 0.4 g [5]. For the trailer trips, the maximum longitudinal acceleration during braking was 0.36 g, while during accelerations, it was 0.34 g. These values were lower than the range of 0.42-0.46 g reported in an earlier study [9,10].…”
Section: The Maximum Horizontal Long-duration Impactsupporting
confidence: 84%
See 2 more Smart Citations